Refining tools for studying cuttlefish ( Sepia officinalis ) reproduction in captivity: in vivo sexual determination, tagging and DNA collection - Sykes, António V. (2018)
To overcome the bottleneck of reproduction in cuttlefish, Sepia officinalis, aquaculture development, there is need for new tools or refinement of methods. While attaining low welfare impact on individuals, procedures to allow for in vivo individual sexual and maturity determination, tagging and collection of samples for high quality DNA are needed. The present study evaluated the use of an endoscope, visual implant elastomer and swabbing for each, respectively, in a set of 3 experiments that registered its effects on growth, mortality and reproduction. Results showed that all the methodologies tested herein were of easy application, did not promote injuries nor poor growth, abnormal reproduction or increased mortality. This indicates that cuttlefish would not be experiencing pain, suffering, distress and lasting harm (PSDLH), resulting from the application of these procedures and that these are therefore recommended as new standards for reproduction studies in the species.